Oxidative stability of sunflower oil under different storage conditions - Laz Mero, Mabel Leonela (2021)
The main alteration of foods that contain oils or fats is due to the oxidation of the fatty acid radicals of the glyceric compounds to form aldehydes, ketones and volatile acids, which are responsible for the unpleasant smell and rancid taste, generating rejection in the consumers. Therefore, the objective of the research consisted in evaluating the oxidative stability of sunflower oil in different storage conditions (capped containers and uncapped containers) and under controlled environmental conditions (27 ± 2 °C; HR: 75 ± 10%). The follow-up was performed with constant periods, monitoring the oxidation through the peroxide index described by the American Oil Chemists’ Society (AOCS), using the Kruskal Wallis test to statistically analyze the data; showing that during the weeks evaluated there was no significant difference (p>0.05). However, under the storage conditions there was a significant difference (p<0.05), with which greater oxidative stability of sunflower oil was determined with capped containers as opposed to uncapped ones.